2005
DOI: 10.1111/j.1365-2915.2005.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

A defensin‐like gene expressed in the black‐legged tick, Ixodes scapularis

Abstract: The black-legged tick Ixodes scapularis Linnaeus (Acari: Ixodidae) is an important vector of microbial pathogens. Knowledge of the tick's innate immune response, particularly defensin and other antimicrobial peptides, is important for understanding how microbes survive in this tick. A defensin gene (slnA) from I. scapularis was obtained by reverse transcription-polymerase chain reaction (RT-PCR) using mRNA extracted from tissues of female ticks. RT-PCR indicated the gene was expressed in the midgut, haemocytes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
55
0
1

Year Published

2006
2006
2013
2013

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 21 publications
2
55
0
1
Order By: Relevance
“…Tick saliva contains bioactive molecules and a plethora of proteolytic enzymes (19,75). Whether tick-derived elements, host-derived products acquired from the tick's blood meal, or salivary gland factors (18,19,34,75,81,82) were responsible for the reduced survival of the plzA mutant in the ticks remains to be determined. We and others have shown that B. burgdorferi uses different mechanisms to survive in different hosts (ticks/mammalian).…”
Section: Discussionmentioning
confidence: 99%
“…Tick saliva contains bioactive molecules and a plethora of proteolytic enzymes (19,75). Whether tick-derived elements, host-derived products acquired from the tick's blood meal, or salivary gland factors (18,19,34,75,81,82) were responsible for the reduced survival of the plzA mutant in the ticks remains to be determined. We and others have shown that B. burgdorferi uses different mechanisms to survive in different hosts (ticks/mammalian).…”
Section: Discussionmentioning
confidence: 99%
“…During acquisition, spirochetes first encounter these molecules as they migrate into the feeding site, while spirochetes within flat nymphs (or larvae infected by immersion) would encounter these ligands solely within the midgut (3). The Hk1/Rrp1-directed synthesis of c-di-GMP initiates an adaptive response that enables spirochetes either to evade killing by noxious substances within midgut epithelium as feeding progresses (21,37,50,73,74) or to adjust metabolically to growth within the arthropod vector. In contrast to the Rrp2/RpoN/RpoS pathway, which is active (ON) only within feeding nymphs, the Hk1/Rrp1 TCS is essential for survival during both the larval and nymphal blood meals.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial challenge causes immunocompetent tissues to produce several soluble antimicrobial factors, including defensin and lysozyme. Defensins are small cationic antimicrobial peptides with activity against gram positive bacteria (2,3) that have been identified in several hard ticks including Dermacentor variabilis (3) and Ixodes scapularis (4,5). Lysozymes hydrolyze the 1-4 β linkage between the N-acetyl-muramic acid and N-acetyl-D-glucosamine residues that make up peptidoglycan in bacterial cell walls (6).…”
Section: Introductionmentioning
confidence: 99%